Community-Based English Training for Enhancing the Professional Competence of Religious Pilgrimage Tour Guides in Palembang - Rahmadila Eka Putri; Welly Ardiansyah; Nurvia Nathasya; Debby Fifiyanti; Faridatuljana Binti Mohd Noor; Priyanka Sasadara Pracena Putri; Marsya Hilwatullisah; Muhammad Rifqi Al Aufa (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Religious tourism constitutes not only a form of spiritual practice but also a channel for cultural diplomacy and global engagement. In Palembang, the annual Ziarah Kubro pilgrimage attracts a growing number of domestic and international visitors. However, limited English proficiency among local pilgrimage guides and pesantren communities constrains the effective communication of religious values, historical narratives, and local wisdom. This community service program aimed to enhance the English communication skills of students at Pesantren Al-Amalul Khair who are directly involved in pilgrimage-related activities, thereby supporting the professionalization of religious tourism services at the community level. The program employed a contextualized English for Tourism framework and commenced with a language needs analysis conducted through field observations, semi-structured interviews, and diagnostic pre-tests to identify participants’ communicative needs. Participants were selected based on their active roles in guiding, hospitality, and religious tourism support. Training activities consisted of role-play simulations of guiding scenarios, guided speaking exercises, visual-based vocabulary instruction, and the collaborative development of bilingual digital brochures. Authentic communicative practice was reinforced through field mentoring during actual pilgrimage activities. Program evaluation was carried out using pre- and post-test, performance-based observation, and qualitative participant feedback. The findings indicated marked improvements in vocabulary mastery, functional guiding expressions, cultural interpretation abilities, and communicative confidence among participants. To ensure sustainability, the program facilitated the establishment of an English Club and provided bilingual learning resources tailored to religious tourism contexts. Overall, the program demonstrates that context-based English training integrated into community practices can effectively strengthen local capacity, enhance community engagement, and support the development of religious tourism services with global orientation.